A prospective study of patient safety incidents in gastrointestinal endoscopy - Matharoo, Manmeet; Haycock, Adam; Sevdalis, Nick; Thomas-Gibson, Siwan (Endoscopy International Open, 2017)
Background and study aims Medical error occurs frequently with significant morbidity and mortality. This study aime to assess the frequency and type of endoscopy patient safety incidents (PSIs).Patients and methods A prospective observational study of PSIs in routine diagnostic and therapeutic endoscopy was undertaken in a secondary and tertiary care center. Observations were undertaken within the endoscopy suite across pre-procedure, intra-procedure and post-procedure phases of care. Experienced (Consultant-level) and trainee endoscopists from medical, surgical, and nursing specialities were included. PSIs were defined as any safety issue that had the potential to or directly adversely affected patient care: PSIs included near misses, complications, adverse events and “never events”. PSIs were reviewed by an expert panel and categorized for severity and nature via expert consensus. Results One hundred and forty procedures (92 diagnostic, 48 therapeutic) over 37 lists (experienced operators n = 25, trainees n = 12) were analyzed. One hundred forty PSIs were identified (median 1 per procedure, range 0 – 7). Eighty-six PSIs (61 %) occurred in 48 therapeutic procedures. Zero PSIs were detected in 13 diagnostic procedures. 21 (15 %) PSIs were categorized as severe and 12 (9 %) had the potential to be “never events,” including patient misidentification and wrong procedure. Forty PSIs (28 %) were of intermediate severity and 78 (56 %) were minor. Oxygen monitoring PSIs occurred most frequently.Conclusion This is the first study documenting the range and frequency of PSIs in endoscopy. Although many errors are minor without immediate consequence, further work should identify whether prevention of such recurrent errors affects the incidence of severe errors, thus improving safety and quality.